A STUDY ON ETHICAL ISSUES IN ADVERTISING: AN INDIAN PERSPECTIVE - Malhotra, Parul (Journal of Advanced Research in Journalism & Mass Communication, 2021)
Today Indian advertising industry is growing at a fast speed. It is affecting all whether a marketer, a consumer, retailers or wholesalers, nobody has escaped from its influence. It is beneficial for economy as well as society. As every coin has two sides; advertising world is also being criticized for its unethical practices like puffery, obscenity, vulgarity, creating materialistic demands, stereotyping and for putting out misleading or exaggerated claims in respect of product, goods and services advertised. The purpose of this study is to understand the ethical issues in Indian Advertising. In this paper we have analyzed with the help of examples the different unethical practices used by advertisers in advertisements in India and also discussed some real life cases solved by CCC (Consumer complaint council) following the necessary ASCI Codes. How to cite this article: Malhotra P. A Study on Ethical Issues in Advertising: An Indian Perspective. J Adv Res Jrnl Mass Comm 2021; 8(1): 1-6.